PERSPEKTIF MANAJEMEN PENDIDIKAN TERHADAP KETIMPANGAN BEBAN KERJA NON POKOK GURU SD NEGERI; DAMPAKNYA PADA KINERJA PEMBELAJARAN DAN KESEJATERAAN GURU - Rifai Rifai (Jurnal Manajemen Pendidikan, 2026)
The non-primary workload of public primary school (SDN) teachers in Sragen district, including duties as Dapodik operators, BOS/BOSDA treasurers and asset administration officers, often disrupts teachers' focus on the learning process. This study aims to analyze the inequality in the distribution of non-primary workload of public primary school teachers and its impact on learning effectiveness and teacher welfare, from the perspective of Islamic Education Management. The research used a qualitative approach with a document study of regulations (Permendiknas 24/2008, Permendikbud 6/2021, PP 19/2017), secondary data analysis of the Education Office, and limited interviews with public primary school teachers in Sragen District. The results show that there are inequalities in the distribution of additional tasks (such as Dapodik operators and BOS treasurers). This inequality has a double negative impact: reducing teachers' focus on core learning performance and disrupting their psychological well-being. This study offers a value-based solution perspective by integrating the principles of justice (al-'adl) and responsibility (Amanah) from Islamic Education Management as the normative foundation.